Pierwsi rolnicy na Ziemi Kociewskiej - refleksja z najnowszych odkryć archeologicznych - Kochanowski, Marian (Wydawnictwo Naukowe UAM, 2005)
The article is aimed at presentation o f a newly discovered Linear Band Pottery settlement at Kościelna Jania, Smętowo Graniczne commune. The site was excavated during rescue works on the A l highway. It has been the largest settlement o f this culture in the Starogard Lake District explored to date. In 21 excavated features, mainly settlement pits, numerous pottery sherds and animal bones (post-consumption remains) were found. Pottery technology and decoration make possible to link these materials with the Note phase and date them back to 430CM1000 be.
First farmers of the Kociewie Land - a reflection after new archaeological discoveries